دليل الحج والعمرة - شاور, ايناس; الدويك, سماح; دنديس, ميساء (Palestine Polytechnic University , department of information technology)
The project is guide for pilgrims in which represent application for smart phones that rectify creation guidelines and clarifications for rituals which requires on the user to work on time where the application will be linked to almanac determines the appropriate time to create each step through show of rites in serialized way "sequentially”. As also provides counter for cruising and the strolling .The advantage of this application that uses the locator (GPS) to determine the users location, where the application after determining the location on showing some information about the place that the user will be in, and display the rituals that it request to do it and the especially invocations in this place .Furthermore the possibility to use the application without the need for the existence of the internet. The application screens will be easy friendly services to the users and clear; because uses of all ages and includes the elderly in which the application contains on sound property that to read the rituals and invocations to help the elderly or those who can't read. المشروع هو دليل للحجاج و للمعتمرين حيث يمثل تطبيق للهواتف الذكية والذي يقوم بوضع إرشادات وتوضيحات بالمناسك التي يتطلب على المستخدم عملها بالوقت المحدد ،حيث تم ربط التطبيق بتقويم يحدد الوقت المناسب لعمل كل خطوه من خلال عرض المناسك بشكل متسلسل. كما ويوفر عداد للطواف و السعي. وميزة هذا التطبيق انه يستخدم محدد المواقع GPS )Global Positioning System( لتحديد موقع المستخدم, حيث يقوم التطبيق بعد تحديد الموقع على عرض نبذة عن المكان المتواجد فيه وعرض المناسك المطلوب أدائها والأدعية الخاصة في ذلك المكان, بالإضافة إلى ذلك إمكانية استخدام التطبيق دون الحاجة لوجود الانترنت. تتميز شاشات التطبيق بأنها سهلة الاستخدام وواضحة لان المستخدمين من مختلف الأعمار ويشمل كبار السن, حيث يحتوي التطبيق على خاصية الصوت لقراءة المناسك والأدعية لمساعدة كبار السن أو من لا يستطيع القراءة.
CD , Number of page 37, تكنولوجيا المعلومات 5/2016
Keywords: دليل ، الحج ، العمرة